Photocatalytic Response of Flash-Lamp-Annealed Titanium Oxide Films Produced by Oblique-Angle Deposition - Raúl Gago; Slawomir Prucnal; Francisco Javier Palomares; Leopoldo Álvarez-Fraga; Ana Castellanos-Aliaga; David G. Calatayud (Nanomaterials)
We report the photocatalytic (PC) response of titanium oxide (TiOx) films grown by reactive DC magnetron sputtering under oblique-angle-deposition (OAD) and subjected to post-deposition flash-lamp-annealing (FLA). Under ballistic growth conditions, OAD yields TiOx films with either compact or inclined columnar structure as the deposition incidence angle (α) with respect to the substrate normal varies from zero to grazing. On the one hand, films produced for α ≤ 45° display a compact and opaque structure comprising the formation of nanocrystalline cubic titanium monoxide (c-TiO) phase. On the other hand, films grown at larger α (≥60°) display tilted columns with amorphous structure, yielding highly porous films and an increased transparency for α > 75°. For TiOx films grown at large α, FLA induces phase transformation to nanocrystalline anatase from the amorphous state. In contrast to as-grown samples, FLA samples display PC activity as assessed by bleaching of methyl orange dye. The best PC performance is attained for an intermediate situation (α = 60–75°) between compact and columnar structures. The obtained photoactivity is discussed in terms of the different microstructures obtained by OAD and posterior phase formation upon FLA.